Nonglaucomatous optic neuropathies in Port Harcourt - Pedro-Egbe CN (Dove Medical Press, 2011)
Chinyere Nnenne Pedro-Egbe1, SAH Cookey2, Elizabeth A Awoyesuku3, Nnenne Ani4 1Ophthalmology Unit, 2Department of Surgery, 3College of Health Sciences, University of Port Harcourt, 4Department of Ophthalmology, University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria Aim: To review the types of nonglaucomatous optic neuropathies seen in Port Harcourt, Nigeria. Materials and methods: Medical case records of all cases of nonglaucomatous optic neuropathy seen in the Eye Clinic of University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria over a 5-year period were reviewed. Relevant data including patient demography, presenting visual acuity and intraocular pressure, and fundus findings were extracted. Other details included central visual field analysis and color vision results. Cases of glaucomatous optic neuropathy were excluded. Results: Ninety-nine cases of optic neuropathy were seen over this time period. There were 52 (52.5%) males and 47 females. The mean age of those with optic neuropathy was 40 ± 18.774 years. Twenty-two patients (22.2%) had bilateral involvement, while the rest were unilateral. About 40% of the patients with optic neuropathies had optic atrophy. Nutritional causes accounted for 31.3% and optic neuritis 27.3%. Over 60% of the patients presented with visual acuities ≤6/60. Most patients (40%) had cecocentral scotoma. Conclusion: Nonglaucomatous optic neuropathies resulting in optic atrophy is not uncommon in our environment and several factors may be implicated but the actual cause is difficult to determine because of late presentation of most patients. Keywords: nonglaucomatous, optic neuropathies, Port Harcourt